2023
DOI: 10.1021/acs.iecr.3c00301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MAl2O4(M = Mg, Co, Ni, Zn, Ba) Nanopowders by Liquid Impregnation of Nanofibrous Alumina

Abstract: We report on a controlled synthesis of MAl2O4 (M = Mg, Co, Ni, Zn, Ba) nanopowders. The method includes three main steps: (i) growth of ultraporous nanofibrous Al2O3 (UPA) monoliths and their preliminary thermal treatment to remove the adsorbed and structural water, (ii) liquid-phase M-nitrate impregnation, and (iii) heat treatment allowing to form desirable nanocrystallites. Small crystallites with a spinel structure and mean size below 10 nm were obtained in Mg, Ni, and Zn aluminates after heat treatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…(AB 2 O 4 ) type oxides are considered to be promising catalysts for the catalytic oxidation of VOCs due to the electron tunability of their metal elements, which can effectively improve the redox capacity and oxygen mobility of catalysts. The modification of spinel catalysts generally revolves around the construction of defects, A and B site element replacement, morphological design, and other methods. In recent years, it has been found that controlling the dispersion state and crystalline structure of the spinel to modulate the electronic structure of the metal ions can effectively advance the redox cycle and active site status in spinel catalysts, and impact the behavior of the reactants on the surface of the catalyst, so as to control the reaction activity . Enhancing the dispersion of the spinel is a common choice to modulate catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…(AB 2 O 4 ) type oxides are considered to be promising catalysts for the catalytic oxidation of VOCs due to the electron tunability of their metal elements, which can effectively improve the redox capacity and oxygen mobility of catalysts. The modification of spinel catalysts generally revolves around the construction of defects, A and B site element replacement, morphological design, and other methods. In recent years, it has been found that controlling the dispersion state and crystalline structure of the spinel to modulate the electronic structure of the metal ions can effectively advance the redox cycle and active site status in spinel catalysts, and impact the behavior of the reactants on the surface of the catalyst, so as to control the reaction activity . Enhancing the dispersion of the spinel is a common choice to modulate catalytic activity.…”
Section: Introductionmentioning
confidence: 99%